Altered type II interferon precedes autoantibody accrual and elevated type I interferon activity prior to systemic lupus erythematosus classification. Issue 11 (25th January 2016) - Munroe, Melissa E; Lu, Rufei; Zhao, Yan D; Fife, Dustin A; Robertson, Julie M; Guthridge, Joel M; Niewold, Timothy B; Tsokos, George C; Keith, Michael P; Harley, John B; James, Judith A
Abstract : Objectives: The relationship of immune dysregulation and autoantibody production that may contribute to systemic lupus erythematosus (SLE) pathogenesis is unknown. This study evaluates the individual and combined contributions of autoantibodies, type I interferon (IFN-α) activity, and IFN-associated soluble mediators to disease development leading to SLE. Methods: Serial serum specimens from 55 individuals collected prior to SLE classification (average timespan=4.3 years) and unaffected healthy controls matched by age (±5 years), gender, race and time of sample procurement were obtained from the Department of Defense Serum Repository. Levels of serum IFN-α activity, IFN-associated mediators and autoantibodies were evaluated and temporal relationships assessed by growth curve modelling, path analysis, analysis of covariance and random forest models. Results: In cases, but not matched controls, autoantibody specificities and IFN-associated mediators accumulated over a period of years, plateauing near the time of disease classification (p<0.001). Autoantibody positivity coincided with or followed type II IFN dysregulation, preceding IFN-α activity in growth curve models, with elevated IFN-α activity and B-lymphocyte stimulator levels occurring shortly before SLE classification (p≤0.005). Cases were distinguished by multivariate random forest models incorporating IFN-γ, macrophage chemoattractant protein (MCP)-3, anti-chromatin and anti-spliceosome antibodies (accuracy 93% >4 years pre-classification; 97% within 2 years of SLE classification). Conclusions: Years before SLE classification, enhancement of the type II IFN pathway allows for accumulation of autoantibodies and subsequent elevations in IFN-α activity immediately preceding SLE classification. Perturbations in select immunological processes may help identify at-risk individuals for further clinical evaluation or participation in prospective intervention trials.